Primary gastric tuberculosis mimicking gastric cancer: a case report - Abdolkarim Ghadimi Moghadam; Abdolvahab Alborzi; Gholam Pouladfar; Ahmad Monabati (Journal of Infection in Developing Countries)
Gastric tuberculosis is an uncommon manifestation of extra-pulmonary tuberculosis infection. The clinical signs of this type of infection are nonspecific and misleading. Clinically gastric tuberculosis resembles peptic ulcer disease or malignancy. We report a case of gastric tuberculosis, which was treated as acid peptic disease, in an Iranian immunocompetent adult with no pulmonary tuberculosis, who received surgery for gastric cancer. Diagnosis was based on PCR despite the detection of negative acid-fast bacilli in the histopathologic specimen. We recommend PCR for Mycobacterium tuberculosis to be done when granuloma or caseation is detected on biopsy in patients who are suspected of having gastric malignancy or acid peptic diseases.